Hit me with your best shot: The link between Chronic Traumatic Encephalopathy (CTE) and dementia in contact-sport athletes - Stanek, Anna (Université d'Ottawa | University of Ottawa, 2013)
Dementia is an umbrella term referring to a set of cognitive and behavioral signs and symptoms associated with neurodegeneration. These signs and symptoms may be indicative of a number of different conditions, each with unique risk factors. A review of the literature was conducted to explore the link between symptoms of dementia and Chronic Traumatic Encephalopathy (CTE) as a result of repeated traumatic brain injury (TBI) in contact-sport athletes. CTE was first described by Martland in 1928 as “Punch-Drunk Syndrome.” Initially thought to be found only in amateur and professional boxers, this condition became known as CTE when symptoms of neurodegeneration began presenting in other contact-sport athletes; including football, hockey, rugby, soccer, and wrestlers. Because the clinical presentation of CTE is similar to many other neurodegenerative diseases, formal clinical diagnostic criteria for CTE does not exist. In the review, articles which addressed CTE symptomology from a pre-mortem psychological perspective were included. 8 articles met the inclusion criteria and employed a variety of methodologies. The majority noted issues with short-term memory deficits, emotional control, task monitoring, and motor dysfunction in athletes with CTE or individuals with a history of repeated traumatic brain injury. The observed symptoms suggest that CTE results in the development of dementia symptoms. While the literature suggests that an association exists, it has limited diagnostic utility due to the absence of unique symptoms. Efforts should be directed towards the identification of diagnostic pre-mortem biomarkers.